Vulvovaginal Laceration and Pelvic Fracture With Symphisiolysis - Karina Surakusuma; Yulia Margaretha (Syntax Literate, 2023)
Vulvovaginal laceration and pelvic fracture with symphysis disruption represent a complex and challenging clinical scenario in the field of obstetrics and gynecology. This study aims to examine the incidence, clinical characteristics, and management strategies for cases involving simultaneous vulvovaginal lacerations and pelvic fractures with symphysis disruption. A retrospective analysis was conducted on a cohort of patients presenting with these combined injuries over a specified period. Demographic data, obstetric history, mode of delivery, associated risk factors, clinical presentation, radiological findings, and management outcomes were systematically reviewed. Results revealed that the occurrence of vulvovaginal laceration and pelvic fracture with symphysis disruption is relatively rare but can lead to significant morbidity. The majority of cases were associated with traumatic childbirth, instrumental deliveries, or pelvic trauma. Prompt diagnosis through a multidisciplinary approach involving obstetricians, orthopedic surgeons, and radiologists is crucial for optimizing patient outcomes. In conclusion, vulvovaginal laceration and pelvic fracture with symphysis disruption present a complex clinical scenario that requires a comprehensive and multidisciplinary approach. Further research and collaborative efforts are warranted to enhance our understanding of risk factors, refine diagnostic protocols, and establish evidence-based guidelines for optimal management of this unique obstetric and gynecologic challenge.